White electroluminescence of diamond/ZnSe composite film - Wang, Sheng-Wei; Wang, Xiao-Ping; Wang, Li-Jun; He, Yu-Zheng; Chang, Jun-Li (Diamond and related materials, 2023)
The diamond/ZnSe/ITO composite film (DZSCF) electroluminescence (EL) device was deposited on n-type heavily doped silicon substrate by microwave plasma chemical vapor deposition technique and vacuum electron beam vapor deposition technique. Its composition, microstructure, current-voltage characteristic and EL characteristic were characterized with a series of corresponding detection equipment. The experimental results show that the device can emit strong white light at a forward applied voltage of 240 V, and its CIE coordinates (0.361,0.334) show that its white light purity is higher and its corresponding color temperature is lower(4271 K). The EL spectra of the device show two broad peaks in the blue-green region (central wavelength at 496 nm) and the red region (central wavelength at 660 nm), respectively. In addition, the device also exhibits obvious rectification characteristics. The corresponding experimental results are explained reasonably. [Display omitted] •A diamond/ZnSe composite film EL device was made. The device can emit strong white light visible to the naked eye.•The electron acceleration effect of diamond layer effectively improve the EL intensity of ZnSe layer.•This study provides a new possible way to achieve high luminance white electroluminescent based on diamond thin film.